«The Great» dyke of the Bug area - V. A. Entin; O. B. Gintov; S. V. Mychak; V. N. Belskyi; Yu. V. Geyko; E. B. Polyachenko; S. I. Guskov; A. V. Marchenko (Геофизический журнал, 2019)
New data of geophysical, geochemical and petrologic studies of the well-known elongated 35km long linear geological structure of predictable fault-dyke nature in crystalline basement of the west part of the Bug mining area (Middle Bug area, the Ukrainian shield) have been considered.  According to the data of surface magnetic mapping of the scale 1:50 000 the structure is clearly marked in magnetic field by the linear anomaly, up to 1,5 km wide, and intensity not more than 1000 nT, but practically not pronounced in gravity field. The strike of the structure (NE 69°) is cross-secting to general latitudinal and northwestern direction of geological formations of the studied region. According to the same data, the northwestern flank of the mentioned band of magnetic maxima is accompanied by more than 40 km long clearly pronounced linear minimum corresponding to axial part of the thick inter-block Mankivska fault zone. According to geophysical features, tectonophysical dimensions, extension and direction this tectonic lineament did not have any analogues in the western part of the USh up to now. Spatial-genetic relation of the studied structure and fault zone has been ascertained. Three geochemical Au anomalies have been ascertained in the weathering crust and zone of disintegration of crystalline rocks of the studied structure by geochemical mapping. It is one third of the total number of Au geochemical anomalies revealed by this mapping within the western part of the Bug mining area. Au was observed in complex with highly contrasting anomalies of Mn, Be, P, Zr, Cr, Ni, Co. However geological nature of the studied geochemical anomaly has not been ascertained by geochemical mapping (drilling with core hydro-transportation without entrance into fresh crystalline rocks). Modern works within the northwestern exocontract of this structure a dyke of the unknown in this area crystalline rocks has been found in an exposure among granitoids of the Uman and Gaysyn complexes which could be determined according to the data of microscopic and microprobe studies, chemical analyses, magnetic and density properties (χ=(40―60)×10–3 SI units; s=2,84 g/sm3) as lamprophyres (spessartite). The studies of enclosing granitoids in contact zone with lamprophyres indicates their active dynamometamorohic and, especially, metasomatic transformation, resulted in their saturation with ferromagnetic, stipulating totally increased magnetization of these formations. Further studies of this structure are recommended both in scientific and exploration purposes.